Objective responsibility in traffic law (Academic Journal of Internal Affairs, 2011)
Objective responsibility appeared as a new institution in traffic law. It puts vehicle operators in the centre of legal responsibility. The new laws introduce grading and fixed amounts of penalties and in an innovative manner require the documentation of damages by technical equipment. Objective responsibility now has a history of two years, and its shortcomings have also become apparent. Despite a Constitutional Court decision on the issue last year, there are still several points where safety requires further corrections. The authors point to possible areas where harmonize legislation.
Keywords: objective responsibility; KRESZ; fine